A new species of stygobitic freshwater crab of the genus Rodriguezia Bott, 1969 (Crustacea: Decapoda: Trichodactylidae) from Tabasco, Mexico - Alvarez, Fernando; Villalobos, José Luis (Zootaxa, 2018)
A new species of freshwater crab of the family Trichodactylidae, genus Rodriguezia Bott, 1969 is described from Grutas de Agua Blanca in southern Tabasco, Mexico. Rodriguezia is a genus endemic to northern Chiapas and southern Tabasco, distributed over a small area of 70 km. Rodriguezia adani n. sp., the third species of the genus, occurs north of its two congeners, being stygobitic with obvious adaptations to cave life. It can be distinguished from R. villalobosi, an epigean species, by the absence of eyes, lack of pigmentation and elongation of the pereiopods; and from R. mensabak by having less elongated pereiopods relative to carapace breadth, an extremely reduced ocular peduncle, and a smaller adult size.